Altered Monocytic Phenotypes are Associated with Uraemic Pruritus in Patients Receiving Haemodialysis - Mei-Ju Ko; Wan-Chuan Tsai; Yu-Sen Peng; Shih-Ping Hsu; Mei-Fen Pai; Ju-Yeh Yang; Hon-Yen Wu; Yen-Ling Chiu (Medical Journals Sweden, 2021)
Uraemic pruritus is one of the most bothersome symptoms in patients receiving haemodialysis. A total of 175 patients receiving maintenance haemodialysis, with 74 patients experiencing uraemic pruritus, were prospectively recruited to assess the influence of the phenotype of blood monocytes and various cytokines on uraemic pruritus. The phenotype of blood monocytes was determined by flow cytometry as classical (CD14++CD16−) monocytes, non-classical (CD14+CD16++) monocytes, and intermediate (CD14++CD16+) monocytes. Eight cytokines, including interleukin (IL)-2, interferon-γ, IL-12p70, IL-4, IL-5, IL-6, tumour necrosis factor-α, and IL-10, were simultaneously detected with a multiplex bead-based immunoassay. Multivariate linear regression analysis showed that a higher percentage of intermediate monocytes (effect estimate 0.08; 95% confidence interval 0.01-0.16) were independent predictors of a higher visual analogue scale score for pruritus intensity. No differences were noted for all 8 cytokines between patients with and without uraemic pruritus. The results of this study indicate that altered monocytic phenotypes could play a role in uraemic pruritus.